Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203449974
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires

Black feminist thought: Knowledge, consciousness, and the politics of empowerment - Hill Collins, Patricia (Routledge, 2000)
A revision of a hugely successful book; this is the 'bible' of contemporary black feminist thought and is widely cited and taught as a seminal text. Completely up-to-date with recent events, trends in popular culture, current events, and politics.
Première publication : 1990 Édition 10e anniversaire
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; discipline; féminismes noirs; incontournable; intersectionnalité; justice sociale; militance; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie; états-unis

Expériences des femmes et théologie. La théologie « mujerista » : une nouvelle pratique théologique - Melançon, Louise (Laval théologique et philosophique, 2000)
Les théologies féministes sont plurielles de par la diversité des expériences qui leur donnent naissance. S'il est vrai que l'expérience du sexisme et de l'androcentrisme traverse les discours féministes, elle n 'en est pas moins contextuelle. La prise en compte de ces expériences des femmes en théologie interroge et commence à modifier la pratique même de la théologie. La théologie mujerista née de la survie des femmes hispano-américaines en est un exemple remarquable.
Keywords: amérique latine; amériques; approches et analyses; cours; discipline; fem1000; femmes*; intersectionnalité; inégalités; premier cycle; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; systèmes d'oppressions; théologie; états-unis

Feminism and the body - Schiebinger, Londa (Oxford University Press, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Section: IX, 500 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme